Comportamento e capacidade resistente de vigas celulares em aço de alta resistência - Pazin, Vítor Augusto (Universidade Federal de São Carlos, 2025)
Steel cellular beams are characterized by profiles with sequential circular openings in the web, resulting in structural elements capable of spanning large distances, providing greater flexural stiffness, and enabling faster construction. Worldwide, studies on cellular beams are largely limited to normal strength steels. In Brazil, research on this type of beam is scarce and relatively recent. Thus, the use of high-strength steels, with yield strength exceeding 460 MPa, in cellular beams remains unexplored. The application of high-strength steels contributes to sustainability due to the reduction of the carbon footprint. Although their use in cellular beams is attractive from both structural and sustainability perspectives, such steels are not addressed by NBR 8800 (ABNT, 2024). The same limitation applies to cellular beams. This research aims to investigate the influence of steel strength variation on the failure modes and structural behavior of high-strength steel cellular beams under simply supported conditions. For this purpose, cellular beams were modeled using the ABAQUS® software, and the results were compared with the design procedures of BS EN 1993-1-13 (ECS, 2024). Given the lack of experimental data on high-strength steel cellular beams, the numerical model validation was conducted in two stages: considering high-strength steel solid-webbed beams and cellular beams made of normal strength steel. The sensitivity analysis of geometric imperfections and residual stresses in high-strength steel cellular beams showed that the influence of residual stresses decreases as steel strength increases. Moreover, the results indicated that the residual stress model accounting for the manufacturing process of normal strength steel cellular beams can be effectively applied to describe residual stresses in high-strength steel cellular beams. The parametric study demonstrated that increasing steel strength may alter the failure mode, as numerical models exhibiting interaction between local and global instabilities may develop only global instabilities as steel grade increases. The use of high-strength steels proved more relevant for less slender cellular beams, in which local failure modes governed the load-bearing capacity. For slenderer beams, effectiveness was reduced, as the increase in resistance capacity was often marginal compared to the gain associated with the higher strength steel. Furthermore, the use of reduced web-posts due to closely spaced openings, combined with the absence of stiffeners, may lead to the occurrence of web-post buckling under compressive stresses.
Behavior and resistance capacity of high-strength steel cellular beams
Keywords: Vigas celulares de aço; Aços de alta resistência; Instabilidade; Simulação numérica; Tensões residuais; Imperfeições geométricas; Steel cellular beams; High-strength steel; Buckling; Numerical modeling; Residual stresses; Geometric imperfections; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS